2016
DOI: 10.1007/s12161-016-0497-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Impurities in Fresh Shrimp Using Improved Majority Scheme-Based Classifier

Abstract: The efficient removal of impurities from postharvest raw shrimp is beneficial to improve the quality of shrimp products. Single feature combined with single classifier results in poor classification rate. Moreover, accuracy of combined classifiers remains unsatisfactory, especially when sound shrimp is mixed with various defective shrimp and impurities. In this study, an improved majority rule (IMAJ) classifier combination scheme was proposed to address this problem. The accuracy of IMAJ (91.53 %) was compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Rossi et al [ 26 ] also developed another system for the identification of fish species called FishAPP using a machine vision system coupled with ANN. Liu et al [ 27 ] used a machine vision system and improved the majority rule (IMAJ) classifier to identify impurities in fresh shrimp. They showed that IMAJ based classifier combined with parallel features are superior (91.53%) over other fusion rule-based classifiers.…”
Section: Introductionmentioning
confidence: 99%
“…Rossi et al [ 26 ] also developed another system for the identification of fish species called FishAPP using a machine vision system coupled with ANN. Liu et al [ 27 ] used a machine vision system and improved the majority rule (IMAJ) classifier to identify impurities in fresh shrimp. They showed that IMAJ based classifier combined with parallel features are superior (91.53%) over other fusion rule-based classifiers.…”
Section: Introductionmentioning
confidence: 99%
“…Although the proposed method is costly, however, the segmentation time is fully competent to perform signals transmission from industrial computer to single-chip in the on-line quality detection and classification system. That is because it has a short distance for object transportation from the stage of capturing image to the stage of actuator [30,31]. In recent years, with the development of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In [20], a joint feature extraction method that is associated with a single classifier is addressed, which has a low classification rate. This work mainly focused on classification of impurities presented in the fresh shrimps.…”
Section: Related Workmentioning
confidence: 99%